The Influence of Work Environment, Work Discipline, and Work Ethic on Employee Performance with Work Motivation as Mediation: A Study at PT. BRI Gorontalo Branch - Haryobismo, Joseph Gemilang; Subyantoro, Arief; Kristanto, R. Heru (Strata International Journal of Social Issues, 2025)
This study examines the influence of work environment, work discipline and work ethic on employee performance with work motivation as a mediator. The research sample consisted of 75 respondents at PT. Bank Rakyat Indonesia Gorontalo Branch. Data analysis techniques using smart Pls 4.0. The results of the study indicate that the work environment has a positive effect on employee performance. Work discipline has a negative effect on employee performance. Work ethic has a negative effect on employee performance. Work discipline has a negative effect on work motivation. Work ethic has a positive effect on work motivation. Work motivation has a positive effect on employee performance. Work motivation does not mediate the positive effect of the work environment on employee performance. Work motivation does not mediate the positive effect of work discipline on employee performance. Work motivation mediates the positive effect of work ethic on employee performance.